The state of the study of comparative public administration in India - Jain, R.B (1991)
The article presents an account of the present state of the study of comparative public administration in India. Imparting a historical perspective, he discusses its evolution in the West emergence of different trends and models, and the problems that were encountered in implementing these models there. Jain makes a broad survey of pioneering empirical studies conducted by Indian scholars in India in this field which followed by another survey on teaching of comparative public administration in India's academic instutions. In the last section of his article, Jain delineates the problems faced by scholars in conducting research in this field, such as non-availability of data across national boundary, prohib
Keywords: Public Administration - India; Public Administration